PHYSIOTHERAPY MANAGEMENT FOR CRUCIATUM LIGAMENTS INJURY IN PHASE 1: A CASE STUDY - Pangestu, Gesang Gede; Perdana, Suryo Saputra; Herman, Dedy (Academic Physiotherapy Conference Proceeding, 2021)
Introduction : ACL injuries represented more than 50% of injuries in the knee and affected more than 200,000 peoples in the United States each year. The ratio of the incidence of ACL injuries in men and women was 66.7% versus 33.3%. The first phase is a key in post operative rehabilitation of cruciate ligament injury. Rehabilitation in the first phase aims to control inflammation, assist the process of tissue formation, protect injury, reduced pain, and muscle activation with isometric. The Problem at the inflammatory stage (phase 1) are usually in the form of uncontrolled inflammation characterized by redness, heat, pain, swelling, and impaired knee function. Case Presentation: Based on the ACL Reconstruction Guidelines Rehabilitation protocol in Skeletally Mature Athletes. A 30-years-old man is a footballer with a weight of 55 kg and a height of 175 cm, complaining of pain and stiffness in his right knee when performing daily activities. On March 25, 2021 the patient experienced a wrong movement in a pivoting position and a collision occurred with another player on the lateral side of the right knee. Management and Outcome :The Patient received physiotherapy program with exercises focusing on swelling and pain management, increasing the range of motion and muscle strength of the right knee and providing a home exercise program according to phase 1 (0-4 weeks). Measurement of swelling with midline, measurement of pain with Numeric Rating Scale and measurement of Range of Motion with Goneometer. Discussion : The patient did physiotherapy sessions twice a week for four weeks. The measurement results showed an increased in the range of motion, a decreased swelling and pain in the right knee. Factors that affected tissue healing including the location of the graft used, management of the preparation of the rehabilitation program, awareness of the patient doing home exercise programs and avoiding contraindications of therapy. Conclusion : The first phase in management of the ligament injury rehabilitation program is very important to accelerate the tissue healing process as well as the requirements for the next phase. If the first phase is not managed properly, there will be a risk of various problems occurring in the subsequent phases and will slow down the tissue healing process and functional activity.